2018
DOI: 10.1007/s11606-018-4649-6
|View full text |Cite
|
Sign up to set email alerts
|

Race and Hepatitis C Care Continuum in an Underserved Birth Cohort

Abstract: BACKGROUND: Birth cohort screening is recommended for hepatitis C virus (HCV) and underserved populations are disproportionally affected by HCV. Little is known about the influence of race on the HCV care continuum in this population. OBJECTIVE: To assess the cascade of HCV care in a large racially diverse and underserved birth cohort. DESIGN: Retrospective cohort study using electronic medical record data abstracted until August 31, 2017. PATIENTS: 34,810 patients born between 1945 and 1965 engaged in primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
46
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 36 publications
5
46
0
2
Order By: Relevance
“…Latina and Asian women in particular were 26%‐55% less likely to receive HCV screening than white women. Although the reasons for this negative association are unclear and may reflect unmeasured factors, it may be related to cultural preferences, social stigma, language barriers that pose difficulty in navigating health systems, and inability or unwillingness to access health care . An additional factor to consider is the higher rates of nontraditional risk factors (such as acupuncture) for HCV infection in Asian populations that may increase the risk of HCV, but may not be recognized as a risk factor by providers .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Latina and Asian women in particular were 26%‐55% less likely to receive HCV screening than white women. Although the reasons for this negative association are unclear and may reflect unmeasured factors, it may be related to cultural preferences, social stigma, language barriers that pose difficulty in navigating health systems, and inability or unwillingness to access health care . An additional factor to consider is the higher rates of nontraditional risk factors (such as acupuncture) for HCV infection in Asian populations that may increase the risk of HCV, but may not be recognized as a risk factor by providers .…”
Section: Discussionmentioning
confidence: 99%
“…This is a retrospective cohort study of a primary care registry that includes electronic medical records of reproductive age women who accessed primary care at least once at one of 12 clinics in the San Francisco Health Network, within the San Francisco Department of Public Health, between December 1, 2016, and December 1, 2018 . Reproductive age women were defined as any female patient between the ages of 15 and 44 years as of December 1, 2018 .…”
Section: Methodsmentioning
confidence: 99%
“…Despite this high screening rate and expanded access to HCV therapy both within liver specialty and primary care settings in this system, only 20.8% of those with documented viremia initiated HCV treatment. Although overall 90.6% achieved SVR, younger age and absence of HIV coinfection were associated with lack of SVR testing that occurred in 8% of those who completed treatment 15 . Wong et al evaluated 29,544 patients chronically infected with HCV across four health systems including two safety-net institutions in the U.S. from January 1, 2011 to February 28, 2017 16 .…”
mentioning
confidence: 94%
“…Continued efforts should be made to increase the rates of HCV screening in underserved populations followed by enrollment into comprehensive treatment and surveillance programs for those newly diagnosed with HCV. We retrospectively evaluated 34,810 birth cohort underserved patients engaged in primary care within the San Francisco’s safety-net healthcare system from October 1, 2014 to October 31, 2016 15 . In this cohort, 99.7% had evidence of HCV screening and 13.8% were HCV antibody positive.…”
mentioning
confidence: 99%
“…Similarly, another study demonstrated increased HCV screening from 1.09 to 2.53 per 100,000 person‐years after release of US Preventive Service Task Force (USPSTF) guidelines, with the most dramatic increase occurring in the Northeast compared to other regions of the country . Despite these increases in HCV screening among baby boomer patients, disparities exist with some subgroups based on age, racial/ethnic minority status, gender, primary care visits, and comorbidities …”
mentioning
confidence: 99%